Surface modification of natural rubber latex films by graft copolymerization - Wang, Peng (Elsevier, 2000)
Surface modification of natural rubber (NR) latex films by argon plasma treatment, as well as by UV-induced graft copolymerization of the plasma-pretreated films with either acrylamide (AAm) or 2,2,3,3,4,4,4-heptafluorobutyl acrylate (HFA), have been carried out to impart new surface properties, such as hydrophilicity or hydrophobicity, on NR latex films. X-ray photoelectron spectroscopy was used to investigate the chemical composition of the modified film surfaces. The peroxide functionalities resulting from surface reaction with air after the Ar plasma treatment greatly facilitated the subsequent UV-induced graft copolymerization. In general, higher monomer concentration, longer UV graft copolymerization time, and longer plasma pretreatment time led to higher graft yield. Contact angle measurements revealed that the hydrophilicity of the NR film surface was considerably enhanced by the plasma treatment and the subsequent graft copolymerization with AAm. On the other hand, water contact angle as large as 109° was achieved for rubber surface graft-copolymerized with HFA. Atomic force microscopic images indicated that surface modification by graft copolymerization had also resulted in a substantial reduction in the surface roughness of the NR latex films.